Concentration-dependent effects of fermented spent coffee grounds and contrasting effects of earthworms on growth and phytochemicals in medicinal plant Glechoma longituba - Bing-Nan Zhao; Zi-Yang Xie; Jia-Ning Liu; Xiao-Ran Chen; Xin-Xin Wang; Jia-Yi Li; Rui Zhang; Chao Si (PLoS ONE, 2025)
Fermented spent coffee grounds (FSCG) serve as a valuable soil amendment to improve soil structure and fertility, while earthworms play a well-established role in enhancing soil processes and plant growth. However, their combined effects on bioactive compound accumulation in medicinal plants remain unclear. This study investigated the individual and interactive effects of FSCG (0%, 10%, and 20%, v/v) and earthworms (with and without Pheretima guillelmi ) on the growth and phytochemical content of Glechoma longituba , a common medicinal herb, under greenhouse conditions. Results showed that 10% FSCG generally promoted plant growth, whereas 20% FSCG generally enhanced the accumulation of total flavonoids, chlorogenic acid, and soluble protein. Earthworms enhanced aboveground biomass and node number but significantly reduced chlorogenic acid content. These findings highlight the potential of FSCG as a sustainable soil amendment in medicinal plant cultivation and underscore the need to consider earthworm activity when optimizing both plant biomass and phytochemical quality.